Teachers' Efforts to Instill Disciplined and Honest Character Education in Elementary Schools - Sari, Yunita Indah (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2018)
This research was conducted with the aim of describing teachers' efforts to instill discipline and honest character education at the Negeri 13/I Muara Bulian elementary school. This research was conducted at SDN 13/I Muara Bulian. This research used a qualitative approach with a type of critical research. The data source in this research is the teacher of classes IB, IIA and III B Negeri 13/I Muara Bulian. Data collection techniques in this research used observation, interviews and documentation. This research uses a validity test, namely Triangulation Technique. Data analysis techniques use Miles and Huberma. The results of the research show that there are six efforts made by teachers to instill discipline and honest character education at SDN 13/1 Muara Bulian. Character education is successful in paying attention to individual differences, so teachers need to do the following things, first, use a variety of character education methods. Both give different tasks for each student. thirdly, modify and enrich teaching materials. The four use varying procedures in making character education assessments and reports. Fifth, understand that students' characters do not develop at the same speed. Sixth, strive for student involvement in various character activities.